Philippine materials in international law - Pangalangan, Raul C. (Leiden Brill Nijhoff, 2022)
"This is a collection of international law materials relating to the Philippines: excerpts of treaties and declarations; international judicial and arbitral decisions; and Philippine constitutional clauses, statutes and Supreme Court decisions. Today new theories abound, calling for comparative perspectives that look at international law through the lens of national and regional practice. This book engages that challenge at a concrete level, e.g., how Marcos's human rights abuses were litigated abroad but never in Philippine courts, and how victim claims for reparations are, ironically, blocked by the Philippine Government citing the Filipino people's competing claims over Marcos's ill-gotten wealth. It retells Philippine history using international law, and re-examines international law using the Philippine experience"--
Constituting the Philippine state in international law-- The armed conflict with the United States before the courts and courts-martial-- National territory-- The Philippines and the International Court of Justice-- Sources of international law-- U.S. military bases-- Human rights cases from the Marcos dictatorship-- Immunities-- Extradition-- International criminal law.
Includes bibliographical references and index.
Keywords: International Court of Justice; Conflict of laws -- Philippines; Human rights -- Philippines; International and municipal law -- Philippines; International criminal law -- Philippines; International law -- Philippines; International law and human rights -- Philippines; Military bases, American -- Philippines